Karakteristik fisika-kimia pengomposan limbah kulit durian (Durio zibethinus L.) menggunakan cairan rumen sapi - Aditya, Anang (Jurnal Protobiont, 2014)
Durian peel is identified to take a long period of time to decay or degradation, thus it requires a pretreatment to simplify the process of hydrolysis. This study aims to determine the condition of chemical physic composting using cow’s rumen liquor. The study used several concentrations and combinations of treatment. Parameters observed in this study include substrate temperature, moisture content, pH, Total Organic C, Total Organic N, and C/N ratio as well. The results obtained i.e. the average temperature of the substrate is 29,090C, the average moisture content of the substrate is 87.55%, and the average pH of the substrate is 7.82. The percentage change of the Organic C is 0.52% for the treatment of 30%. The percentage change of the Organic N is 36.76%. The Percentage change of C/N ratio is 41.36%. These results indicate a distinctive percentage value from various treatments with the highest concentration at 30% of cow’s rumen liquor on Organic C, Organic N as the control, and C/N ratio as well.